S119 Efficacy and feasibility of pulmonary hypertension specific exercise rehabilitation in a uk setting. (December 2018) - MacKenzie, A; Irvine, V; McCaughy, P; Jayasekera, G; Ford, J; Kennedy, F; Crowe, T; Carson, K; Thomson, R; Welsh, D; Brewis, M; Church, C; et al.
Abstract : Introduction: Despite contemporary drug therapy, many patients with pulmonary arterial hypertension (PAH) have a high symptom burden and prognosis remains poor. Single centre studies have demonstrated significant improvements in exercise capacity and Quality of Life (QOL), with PAH specific exercise therapy. The underlying mechanisms of these improvements are unclear and the efficacy outwith an established rehabilitation system has yet to be demonstrated. Aims: Determine the feasibility of a UK PAH–specific exercise rehabilitation programme Generate pilot data to explore mechanisms of improved exercise capacity Methods: 30 Patients with stable, optimally treated pre-capillary pulmonary hypertension were recruited from the Scottish Pulmonary Vascular Unit to a two phase exercise rehabilitation study: Phase 1: 3 weeks of daily, supervised resistance, aerobic and respiratory muscle training Phase 2: 12 weeks of remotely supported exercise mirroring the programme above Patients were allocated to one of two groups A: Immediate entry to exercise programme B: 15 weeks of standard PAH drug therapy, acting as a control group, then crossover entry to the exercise programme Assessments occurred at baseline, after phase 1 and the end of study. Group B patients had an additional assessment after 15 weeks of standard treatment. Primary outcome measures were change in 6 min walk distance (6 MWD) and PAH specific QOL (EMPHASIS) at 15 weeks. Results: Population characteristics: Median age 53, 27% male, 67% IPAH, 22% CTD-PAH, 7% Heritable, 7% CTEPH. Exercise capacity, gas exchange and oxygen delivery improved following completing of the exercise programme (table 1) 6 MWD improved in those undertaking exercise: 41 m (50) compared with the control group 5 m (16). EMPHASIS QOL score also improved −5.8 (11) compared with the control group, 1.2 (5.1), p 0.031. Conclusions: Exercise therapy in a UK PAH population is feasible and efficacious. Gas exchange improvements appear to be a significant contributor to this change, however it is unclear if lung recruitment, breathing efficiency or improved perfusion is responsible. The magnitude of improvement in exercise capacity is smaller than demonstrated in previous studies. Further research is needed to determine the optimal timing and most suitable patients for rehabilitation.